2010
DOI: 10.1002/jor.21278
|View full text |Cite
|
Sign up to set email alerts
|

Motion‐derived coordinate systems reduce inter‐subject variability of elbow flexion kinematics

Abstract: The selection of a joint coordinate system affects the outcome of motion pathways. We developed coordinate systems for the ulna and humerus, which are generated from upper extremity motion. These Motion-Derived Coordinate Systems (CS) were compared to traditional Anatomy-Derived CS created using surface digitizations of anatomical features. Within-subject repeatability of creating MotionDerived CS was quantified. In vitro elbow flexion was generated in the gravity-dependent position using an active upper extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…7 For the humerus, the capitellum surface and the trochlear sulcus were traced, and a point was digitized in the center of the humeral shaft at the mid-diaphysis. The capitellum was sphere fit, the trochlear sulcus was circle fit, and their centers were calculated.…”
Section: Kinematics Measurementsmentioning
confidence: 99%
“…7 For the humerus, the capitellum surface and the trochlear sulcus were traced, and a point was digitized in the center of the humeral shaft at the mid-diaphysis. The capitellum was sphere fit, the trochlear sulcus was circle fit, and their centers were calculated.…”
Section: Kinematics Measurementsmentioning
confidence: 99%
“…The approximate position of the humerus, ulna, and radius coordinate system are also indicated. The definition of the local elbow coordinate systems were obtained from Ferreira et al (2011) ,and Morrey and Chao (1976 3.4. Stiffness parameters for interosseous membrane.…”
Section: IVmentioning
confidence: 99%
“…The contact parameters used for this study are shown in Table 3.5. Local coordinate systems for each bone segment were created as described by Ferreira et al (2011) and Morrey and Chao (1976) to measure the segment motion of the model (Fig. 3.10).…”
Section: Multibody Model Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges also still remain in determining accurate FHAs for investigations of joint kinematics due to inherent tracker error and vibration [8], One available technique to improve the calculated FHAs is the use of a moving window analysis [11,12]. Crawford [11] suggested that an arbitrary window size of ±10 data points spanning each FHA would reduce error; however, this window size may be ineffective for rapid movements or those that have inconsistent angular velocity.…”
Section: Introductionmentioning
confidence: 99%